Ghr-miR5272a-mediated regulation of GhMKK6 gene transcription contributes to the immune response in cotton. (21st October 2017) - Wang, Chen; He, Xiaowen; Wang, Xinxin; Zhang, Shuxin; Guo, Xingqi
Abstract : GhMKK6 and ghr-miR5272a comprise a feedback loop in cotton and ghr-miR5272a-mediated regulation of GhMKK6 expression contributes to the immune response against Fusarium wilt. Abstract: Fusarium wilt is a major biotic stress affecting the productivity of cotton ( Gossypium hirsutum ). Although mitogen-activated protein kinase (MAPK) cascades play critical roles in plant disease resistance, their intricate regulation under fungal stress remains unclear, especially with regards to microRNA-mediated regulation of MAPK gene expression. In this study, we report that the MAPK kinase gene GhMKK6 and ghr-miR5272a work together in cotton resistance to Fusarium wilt. Silencing GhMKK6 in cotton decreased resistance to F. oxysporum by repressing the expression of known disease-resistance genes. Furthermore, although GhMKK6 played a positive role in disease resistance, excessive GhMKK6 activation caused an excessive hypersensitive response. ghr-miR5272a, a major regulator, prevents this excessive response by regulating GhMKK6 expression. ghr-miR5272a targets the GhMKK6 3′-untranslated region in cotton. Overexpressing miR5272a decreased the expression of GhMKK6 and disease-resistance genes, and increased sensitivity to F. oxysporum, yielding a similar phenotype to GhMKK6 -silenced cotton. Overall, these results demonstrate that the ghr-miR5272a-mediated regulation of GhMKK6 expression contributes to the immune response in cotton, and reveal a new feedback loop mechanism in plant disease response.